Fluctuations in Blood Marginal Zone B-Cell Frequencies May Reflect Migratory Patterns Associated with HIV-1 Disease Progression Status. - Julie Gauvin; Josiane Chagnon-Choquet; Johanne Poudrier; Michel Roger; Montreal Primary HIV Infection and Slow Progressor Cohorts (PLoS ONE)
We have previously shown that overexpression of BLyS/BAFF was associated with increased relative frequencies of innate "precursor" marginal zone (MZ)-like B-cells in the blood of HIV-1-infected rapid and classic progressors. However, along with relatively normal BLyS/BAFF expression levels, these cells remain unaltered in elite-controllers (EC), rather, percentages of more mature MZ-like B-cells are decreased in the blood of these individuals. Fluctuations in frequencies of blood MZ-like B-cell populations may reflect migratory patterns associated with disease progression status, suggesting an important role for these cells in HIV-1 pathogenesis. We have therefore longitudinally measured plasma levels of B-tropic chemokines by ELISA-based technology as well as their ligands by flow-cytometry on blood B-cell populations of HIV-1-infected individuals with different rates of disease progression and uninfected controls. Migration potential of B-cell populations from these individuals were determined by chemotaxis assays. We found important modulations of CXCL13-CXCR5, CXCL12-CXCR4/CXCR7, CCL20-CCR6 and CCL25-CCR9 chemokine-axes and increased cell migration patterns in HIV progressors. Interestingly, frequencies of CCR6 expressing cells were significantly elevated within the precursor MZ-like population, consistent with increased migration in response to CCL20. Although we found little modulation of chemokine-axes in EC, cell migration was greater than that observed for uninfected controls, especially for MZ-like B-cells. Overall the immune response against HIV-1 may involve recruitment of MZ-like B-cells to peripheral sites. Moreover, our findings suggest that "regulated" attraction of these cells in a preserved BLyS/BAFF non-inflammatory environment, such as encountered in EC could be beneficial to the battle and even control of HIV.